PLANETARIUM DI YOGYAKARTA LANGGAM CUBISME SEBAGAI TITIK TOLAK DALAM PERANCANGAN - Wahyu Yuliasari; Dwi Hedi Heriyanto; Hari Yuliarso (Universitas Sebelas Maret Surakarta, 2014)
bstract: Planetarium in Yogyakarta is one means of recreation (scientific tourism), which aims to provide a forum for the public to know the information and knowledge about astronomy. The design of the Planetarium in Yogyakarta background with the potential for the city of Yogyakarta as education, cultural cities, and tourist destinations. Furthermore in Yogyakarta there are also a bevy of astronomy called Jogja Astro Club (JAC) to academician , the general public, students and people from all walks of astronomy enthusiasts. One of the main factors is the absence of a container that holds information about astronomy. Design problem that arises is how to apply the constituent elements of the space in the form of massive columns that connect the space inside - outside space with lighting arrangements such as the embodiment of style cubisme. Planetarium in Yogyakarta with cubisme style and the big bang theory emphasizes two things in common namely space, time, and matter. In the Planetarium, cubisme style manifested by the presence of the shape and mass composition (time, circulation and materials), circulation (outside the circulation and circulation within the site) which is a manifestation of the set of spatial planning (materials, space and lighting).Keywords: Planetarium, Scientific Tourism, Potency and Activity Planetarium, Cubisme Style.